Subclonal p53 immunostaining in the diagnosis of endometrial carcinoma molecular subtype - Huvila Jutta; Thompson Emily F.; Vanden Broek Jamie; Lum Amy; Senz Janine; Leung Samuel; Gilks C. Blake; Köbel Martin; McAlpine Jessica N.; Jamieson Amy (WILEY, 2025)
Aims: The significance of subclonal expression of p53 (abrupt transition from wild-type to mutant-pattern staining) is not well understood, and the arbitrary diagnostic cut-off of 10% between NSMP and p53abn molecular subtypes of endometrial carcinoma (EC) has not been critically assessed. Our aim was to characterise subclonal p53 and discrepant p53 expression/TP53 sequencing results in EC and assess their clinical significance.
Methods and results: Subclonal p53 immuostaining on whole sections from 957 ECs was recorded. Agreement between TP53 mutational assessment and p53 immunostaining was evaluated. Subclonal p53 IHC staining was seen in 4.0% (38 of 957) of cases, with 23 of 957 (2.4%) showing mutant-pattern p53 staining in ≥10% of tumour cells. It was most commonly seen in POLEmut (nine of 65, 14%) and MMRd (13 of 274, 4.7%) EC ('multiple classifier' ECs), where subclonal p53 staining does not impact the molecular subtype diagnosis. Excluding POLEmut and MMRd EC, 11 of 957 (1.1%) showed ≥10% subclonal p53 from which four patients died of disease, while there were no deaths due to disease in the five patients with <10% mutant-pattern p53 staining. Agreement between p53 immunostaining and TP53 sequencing was 92.6%; most of the discrepant results were in the ultramutated POLEmut or hypermutated MMRd ECs. In NSMP and p53abn EC the agreement between IHC and sequencing was 95.8%.
Conclusions: Subclonal p53 staining ≥10% is present in only 1.1% of EC after excluding 'multiple classifier' ECs. The cut-off of ≥10% subclonal p53 staining identified patients at increased risk of dying from EC, supporting its use to diagnose p53abn molecular subtype.